THE JURIDICAL ANALYSIS AGAINST DOCUMENT FALSIFICATION IN EXPORT ACTIVITIES OF THE DANGEROUS GOODS CATEGORY: A Case Study of Court Decision on Cassation No. 294 K/PID.SUS/2018 - Napitupulu, Benyamin Steven; Sushanty, Vera Rimbawani (jfpublisher, 2022)
The objective of this research is to examine the causes of document falsification in export activities based on primary legal sources, that is Law No. 10/1995 Article 103 Letter A which has been amended by Law No. 17/2006 concerning of Customs. The scope of this research is self-assessment system that opens a gap in document falsification in customs export activities. The method used in this research is juridical-normative method which include law regulation or it commonly known as statute approach in the applicable export activities and it regulated as norms in Criminal Code which combined with alternative approach used case approach in accordance with the topic of this research, the crime of falsifying export documents under the customs law. Based on the result of this research, it concludes that the self-assessment system is useful to support the speed of the process in increasing the competitiveness of export commodities in Indonesia. Unfortunately, the self-assessment system does not provide a control function on the correctness of document contents, especially for export commodities of dangerous goods.